Nieśmiałość a ocena funkcjonowania w sytuacjach niewymagających ekspozycji społecznej - Studenski, Ryszard; Studenska, Anna (Acta Universitatis Lodziensis. Folia Psychologica, 2010)
Shyness is regarded as a trait which interferes with social functioning. In the presented research the attempt was made to check whether the consequences of shyness manifest themselves outside the domain of social interaction and are visible in self-evaluations of such qualities as resistance to stress, coping with risk, openness to experience and independence. Participants were 174 women and men aged between 18 and 23. Apart from shyness such variables were measured as: temperamental traits (EAS), personality traits (NEO-FFI), risk propensity, the need to change oneself and environment, locus of control, sensation seeking (SSS- V), self – esteem and five factors of learning autonomy. By means of standard multiple regression analysis it was shown that the contribution of temperamental traits in the prediction of shyness is not significantly different in comparison with the contribution of thee Big – Five personality traits. It was also found that shyness is positively correlated with the qualities which affect emotional instability level, i.e. with emotionality – fear, emotionality-distress and with neuroticism. Shyness proved to be negatively correlated with the traits affecting socio-centric behaviour such as sociability and extraversion. It was noticed that the influence of shyness my be transferred outside the social domain. Shy individuals in comparison with the bold ones judged themselves as less prone to take risks, more rarely exhibiting behaviors connected with self-creation and more rarely introducing changes in their environment. Shy persons compared with the bold ones evaluated themselves as having the sense of external locus of control, exhibiting stronger tendency to underestimate their self-esteem and being less open to new experiences and less autonomous in formulating learning goals, in planning their learning and evaluating the effectiveness of learning strategies.